Effect of Zeolite Concentration on Hydrogel Characteristics of Arrowroot-Based Starch-G-Poly(Acrylic Acid)/Zeolite Composite - Sjaifullah, Achmad; Saputra, Beny Akhmat; Adiwinata, I Nyoman; Santoso, Agung Budi; Busroni; Reza, Muhammad (Indonesian Chimica Letters, 2022)
This study aims to synthesize a hydrogel zeolite composite of arrowroot starch graft copolymerized with acrylic acid through a radical polymerization reaction in a water. Various scenarios were tested using different natural zeolite concentration to determine the impact on swelling/water absorption of the composite. The resulting product was a solid gel-the test results showed that the swelling increased as the ratio of starch to acrylic acid decreased. Increased starch concentrations generally lead to decreased water absorption (swelling capacity). Adding a zeolite improved swelling to some extent and the optimum zeolite concentration was 60%. The increased concentration of zeolite also hardened the hydrogel composite. The highest swelling in the hydrogel composite of starch-g-poly(acrylic acid)/zeolite 60% is 1056.25 g.g-1. FTIR analysis of functional groups was conducted to determine differences in the IR spectra of arrowroot starch, acrylic acid, hydrogels, zeolites, and composite hydrogel. Si-O signal appearing on the IR spectra of hydrogel composite with wave number 1030 cm-1 indicates that composite hydrogel with zeolite was synthesized